The socio-ecology and social behaviour of the brown hyaena Hyaena Brunnea, Thunberg, 1820 in the southern Kalahari. - Bothma, Jacobus du P. (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 1981.